Regulation of Decay Accelerating Factor Primes Human Germinal Center B Cells for Phagocytosis - Dernstedt, Andy; Leidig, Jana; Holm, Anna; Kerkman, Priscilla F.; Mjösberg, Jenny; Ahlm, Clas; Henriksson, Johan; Hultdin, Magnus; Forsell, Mattias N. E. (Frontiers in Immunology, 2021)
Germinal centers (GC) are sites for extensive B cell proliferation and homeostasis is maintained by programmed cell death. The complement regulatory protein Decay Accelerating Factor (DAF) blocks complement deposition on host cells and therefore also phagocytosis of cells. Here, we show that B cells downregulate DAF upon BCR engagement and that T cell-dependent stimuli preferentially led to activation of DAFlo B cells. Consistent with this, a majority of light and dark zone GC B cells were DAFlo and susceptible to complement-dependent phagocytosis, as compared with DAFhi GC B cells. We could also show that the DAFhi GC B cell subset had increased expression of the plasma cell marker Blimp-1. DAF expression was also modulated during B cell hematopoiesis in the human bone marrow. Collectively, our results reveal a novel role of DAF to pre-prime activated human B cells for phagocytosis prior to apoptosis.